Co-combustion of coal with printing and dyeing sludge: Numerical simulation of the process and related NOX emissions. (1st January 2015) - Hu, Zhifeng; Ma, Xiaoqian; Chen, Yumeng; Liao, Yanfen; Wu, Jie; Yu, Zhaosheng; Li, Shuangshuang; Yin, Libao; Xu, Qisheng
Highlights: PDS content, moisture content and SA distribution greatly affect the co-combustion. The more the PDS content is, the higher the NOX concentration in global emissions is. There are higher NOX emission and lower temperature under higher moisture content. Blending with 10% PDS of 40% moisture content is feasible and reasonable. The best SA distribution is the ratio (from upper to bottom) of 3:1:2:4. Abstract: The co-combustion of coal with printing and dyeing sludge (PDS) in a pulverized coal power plant was simulated based on the computational fluid dynamics method. The co-combustion characteristics and NOX emissions were analyzed to determine the optimal PDS content, moisture content, and secondary air (SA) distribution scheme. This study comprised three main parts. The first part was a comparative analysis of blending coal with different amounts of PDS, which indicated that the overall temperature level of the furnace decreased slightly and the NOX emissions increased gradually as the PDS content increased. The second part was a comparative analysis of blending coal with PDS at different moisture contents, which indicated that the furnace temperature was lower and the NOX emissions were higher with as the moisture content increased. Furthermore, after analyzing the combustion characteristics and NOX emissions, we found that blending with 10% PDS at a moisture content of 40% was the most reasonable strategy based on a constant total lower calorific value. In the third part, SA optimization analysis indicated that the SA distribution clearly affected the combustion characteristics and pollutant emission, where an SA ratio from top to bottom of 3:1:2:4 was the best SA distribution scheme.